Large B-Cell Lymphoma with T-Cell–Rich Background and Nodules Lacking Follicular Dendritic Cell Meshworks: A Case Report with Complete Response to Chemotherapy and a Review of the Literature - Shalata, Walid; Massalha, Ismaell; Al-Athamen, Kayed (International Journal of Innovative Research in Medical Science, 2020)
In this report, we describe a 38-year-old male with a very rare type of lymphoma, large B cell lymphoma with T cell-rich background and nodules lacking follicular dendritic cell meshworks (THRLBCL). In 2016 the patient presented hot flashes and night sweats (B-symptoms) and peripheral edema. He was treated with R-CHOP (doxorubicin, vincristine, cyclophosphamide, rituximab and Prednisone) chemotherapy, a Positron emission tomography–computed tomography (PET-CT) scan was performed after four cycles of treatment which showed radiologic complete response and blood test (complete blood count (CBC)) results showed normal ranges. As of September, 2020 he patient remains in complete remission. We searched the literature for descriptions of cases spanning the diagnostic spectrum of THRLBCL and we identified only five cases worldwide. The last reported case was in 2014 with distinctive features that were difficult to classify according to the World Health Organization criteria or previously described variants. Our patient is the sixth case of THRLBCL to be reported. He is the youngest of the reported cases and the first from Israel and the Middle East.